The EFFECT OF GROUP COUNSELING SERVICES ON STUDENTS WHO EXPERIENCE DISSOCIATIVE SOCIAL BEHAVIOR IN JUNIOR HIGH SCHOOL - Saputra, Adif Jawadi; Sinthia, Rita; Paryanti, Dini Kusuma; Ibrahim, Iqbal (Prodi Bimbingan dan Konseling Islam, 2024)
This research is motivated by students who experience high dissociative social behavior. The purpose of this study is to describe the effect of group counseling services on students who experience dissociative social behavior at SMP country 02 Kepahiang. This research method uses the experimental method of one group pretest posttest design. The population in this study were students of class VIII A, namely 30 students. The research sample was taken by purposive sampling technique with a sample of 6 students. The data collection technique used a questionnaire with a Likert scale. Data analysis results using (paired sample t-test) and by using the SPSS version 2.1 application. Dissociative social behavior before being given treatment is high. The results obtained in this study indicate an influence. Students’ dissociative social behavior after being given treatment in the form of group counseling. From the results of this study, it is recommended for Guidance and Counseling teachers to use group counseling services to reduce dissociative social behavior in Class VIII A students at SMP country 02 Kepahiang